2016
DOI: 10.1515/pjvs-2016-0036
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonia intracellularis and Porcine Circovirus type-2 infection in Estonia

Abstract: The present study describes the reasons of post-weaning distress in Estonian pig herds. Here we examined the natural cases of Lawsonia intracellularis and porcine circovirus 2 (PCV2) infection and co-infections.The presence of L. intracellularis in swine herds were tested by PCR and by histopathological methods, whereas PCV2 was detected by real-time-PCR and immunohistochemical stainings. Seven of the 11 investigated herds with signs of post-weaning wasting were infected with L. intracellularis and all 11 herd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Upon comparing the available literature, it has been observed that the percentage of L. intracellularis -positive samples by IHC in this particular caseload (57%) is substantially higher than the rates reported in similar field investigations in Denmark (18%) [ 2 ], or in Estonia (22%) [ 9 ]. This discrepancy could be attributed to the criteria used in this investigation to select farms exhibiting anamnesis indicative of L. intracellularis, which may have influenced the outcomes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Upon comparing the available literature, it has been observed that the percentage of L. intracellularis -positive samples by IHC in this particular caseload (57%) is substantially higher than the rates reported in similar field investigations in Denmark (18%) [ 2 ], or in Estonia (22%) [ 9 ]. This discrepancy could be attributed to the criteria used in this investigation to select farms exhibiting anamnesis indicative of L. intracellularis, which may have influenced the outcomes.…”
Section: Discussionmentioning
confidence: 64%
“…These changes can result in potential dysmicrobism and an increased likelihood of co-infections. The most commonly reported co-infections are between PCV2 and Salmonella , Brachyspira spp., and/or L. intracellularis [ 2 , 9 , 10 , 23 ]. Additionally, PCV2 should be considered a primary intestinal pathogen in swine, associated with macroscopic features of necrotic enteritis [ 2 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the outcome of concurrent infections with PCV2 and other pathogens, focusing on the induction of PCVAD, the immunosuppressive role of PCV2 and/or factors that facilitate PCV2 replication ( 10 , 11 , 13 , 16 , 27 , 28 ). In the present study, pigs of high sanitary status were initially exposed to PCV2 and subsequently to a combined L. intracellularis /PCV2 inoculum mirroring the situation often seen under field conditions ( 29 31 ). Similar to a previous study on concurrent inoculation of PCV2 and L. intracellularis ( 13 ), our study showed that prior exposure to PCV2 had no significant impact on the pathological responses to a subsequent combined L. intracellularis /PCV2 inoculation two weeks later.…”
Section: Discussionmentioning
confidence: 86%
“…Infection with virulent PCV2 causes immune suppression in the host animal, which may result in secondary infection with bacteria and/or viruses into the pig population [ 37 , 38 ]. For example, PCV2b infection resulted in pigs becoming susceptible to secondary infection with Lawsonia intracellularis with many pigs showing emaciation, which may be caused by porcine proliferative enteritis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%